2016
DOI: 10.1094/mpmi-09-16-0195-r
|View full text |Cite
|
Sign up to set email alerts
|

Sinorhizobium fredii HH103 Invades Lotus burttii by Crack Entry in a Nod Factor–and Surface Polysaccharide–Dependent Manner

Abstract: Sinorhizobium fredii HH103-Rif, a broad host range rhizobial strain, induces nitrogen-fixing nodules in Lotus burttii but ineffective nodules in L. japonicus. Confocal microscopy studies showed that Mesorhizobium loti MAFF303099 and S. fredii HH103-Rif invade L. burttii roots through infection threads or epidermal cracks, respectively. Infection threads in root hairs were not observed in L. burttii plants inoculated with S. fredii HH103-Rif. A S. fredii HH103-Rif nodA mutant failed to nodulate L. burttii, demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 64 publications
1
60
0
Order By: Relevance
“…S. fredii SVQ318 ( nodD1 ) and SVQ555 ( nodD1 nodD2 ) failed to nodulate L. burttii and L. japonicus Gifu. This result, together with the Nod − phenotype shown by a nodA mutant (Acosta‐Jurado et al, ), further confirmed the strict requirement of Nod‐factors for nodule formation with these two legumes.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…S. fredii SVQ318 ( nodD1 ) and SVQ555 ( nodD1 nodD2 ) failed to nodulate L. burttii and L. japonicus Gifu. This result, together with the Nod − phenotype shown by a nodA mutant (Acosta‐Jurado et al, ), further confirmed the strict requirement of Nod‐factors for nodule formation with these two legumes.…”
Section: Discussionsupporting
confidence: 64%
“…S. fredii HH103 Rif R fails to form nitrogen‐fixing nodules with L. japonicus Gifu but effectively nodulates L. burttii (Sandal et al, ). L. burttii nitrogen‐fixing nodules occupied by HH103 Rif R are the consequence of intercellular bacterial invasion (Acosta‐Jurado et al, ) instead of by the formation of ITs in root hairs. This fact prompted us to investigate how the S. fredii HH103 nodD2 and nolR mutants invade L. japonicus Gifu and L. burttii roots.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some instances, mutations introduced into the host receptors or the corresponding symbiont polysaccharides can lead to rhizobia being diverted from their normal route of intracellular infection (Kawaharada et al ., ). However, the rhizobia can nonetheless form nodules via passive crack entry (Acosta‐Jurado et al ., ), or through reentry into plant cells from intercellular space (Kawaharada et al ., ). Moreover, host control over nodulation specificity can also be overwhelmed.…”
Section: Control and Conflict Over Legume Nodulationmentioning
confidence: 99%